Micro free‐flow isoelectric focusing with integrated optical pH sensors - Nagl, Stefan (Eng Life Sci, 2017)
Recently, a new observation method for monitoring of pH gradients in microfluidic free‐flow electrophoresis has emerged. It is based on the use of chip‐integrated fluorescent or luminescent micro sensor layers. These are able to monitor pH gradients in miniaturized separations in real time and spatially resolved; this is particularly useful in isoelectric focusing. Here these multifunctional microdevices that feature continuous separation, monitoring, and in some instances other functionalities, are reviewed. The employed microfabrication procedures to produce these devices are discussed and the different pH sensor matrices that were integrated and their applications in the separation of different types of biomolecules. The procedures for obtaining spatially resolved information about the separated molecules and the pH at the same time and different detection modalities to achieve this such as deep UV fluorescence as well as time‐resolved referenced pH sensing and the integration of a precolumn labeling step into these platforms are also highlighted.